Apprendre dans des interactions avec de multiples participants : la formation pratique des éducatrices et éducateurs de l’enfance - Marianne Zogmal (Activités)
In Education and Care professions, vocational training frequently occurs in interactions involving multiple participants. Novice workers therefore have to learn to participate in ongoing activities by engaging in work teams and by adjusting to the targeted recipients of the service. At the crossroads of research on work-based learning and interactional perspectives on work analysis, the paper proposes an empirical exploration of the forms of participation of a trainee in childhood education, during an educational activity conducted with a group of children, in the presence of two experienced educators. The notion of Participatory Configuration provides insights on how the different participants establish a definition of the situation and adapt their focus when performing collective activities. In addition, relational positioning occurs through the forms used to address the recipients and the phenomena of facework. At the epistemic level, interactants co-construct shared meaning, made mutually manifest in the interactional flow. Constant changes are part of a dynamic interaction sequence, organized sequentially and simultaneously. Knowing how to participate is therefore part of pragmatic, relational, epistemic and dynamic dimensions of interactions. This interactional perspective aims to shed light on the issues of training situations in workplace contexts with multiple participants.